CLINICAL CASE OF THROMBOLYTIC THERAPY OF RECURRENT ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION IN PATIENT WITH LONG HISTORY OF ISCHEMIC HEART DISEASE - N. T. Vatutin; V. B. Kostogryz; A. I. Kostogryz; O. I. Stolika (Столичная издательская компания, 2016)
Presented case report demonstrates the efficacy and safety of hospital use of thrombolytic agent Fortelizin in pharmaco-invasive strategy for the treatment of a patient with acute myocardial infarction and with a long history of ischemic heart disease and long-term dynamics of the verified angiographic progression of coronary atherosclerosis. Hospital thrombolytic therapy with Fortelizin was vital alternative in case of a substantial time delay in mechanical reperfusion of the myocardium.